INACCURATE REPORTING OF MINERAL COMPOSITION BY COMMERCIAL STONE ANALYSIS LABORATORIES: IMPLICATIONS FOR INFECTION AND METABOLIC STONES - Krambeck, Amy E. (2010)
INTRODUCTION: The goal of this study was to determine the accuracy of stone composition analysis by commercial laboratories. METHODS: 25 human renal stones with infrared spectroscopy (IR) determined compositions were fragmented into aliquots and studied with micro-computed tomography (CT) to ensure fragment similarity. Representative fragments of each stone were submitted to 5 commercial stone laboratories for blinded analysis. RESULTS: All laboratories agreed on composition for 6 pure stones. Of 4 stones known to contain struvite, only 2(50%) were identified as struvite by all laboratories. Struvite was reported as a component by some laboratories for 4 stones previously determined not to contain struvite. Overall, there was disagreement regarding struvite in 6(24%) stones. For 9 calcium oxalate (CaOx) stones, all laboratories reported some mixture of CaOx, but the quantities of subtypes differed significantly among laboratories. In 6 apatite containing stones, apatite was missed by the laboratories in 20% of the samples. None of the laboratories identified atazanavir in a stone containing that antiviral drug. One laboratory reported protein in every sample, while all others reported it in only 1 sample. Nomenclature for apatite differed among laboratories, with one reporting apatite as carbonate apatite (CA) and never hydroxyapatite (HA), another never reporting CA and always reporting HA, and a third reporting CA as apatite with calcium carbonate. CONCLUSIONS: Commercial laboratories reliably recognize pure calculi; however, variability in reporting of mixed calculi suggests a problem with accuracy of stone analysis results. Furthermore, there is a lack of standard nomenclature used by laboratories.